Government Expenditures and Economic Growth: A Nonlinear Causality Investigation for the UK (European Journal of Marketing and Economics, 2019)
This study aims to explore the causal relationship between government expenditures and economic growth in the UK. The analysis emphasizes on the nonlinearity facet of the explored causality. In this aspect, existing conditional heteroscedasticity as a potential source of bias, is filtered out with the use of the nonparametric Diks and Panchenko causality test. The UK government expenditures are disaggregated into total managed expenditure (TGE), current expenditure (CGE) and net investment (IGE), in order to account for a possible heterogeneity in a causality disclosure linked to the nature of expenditures. The findings support that UK government spending Granger causes nonlinearly UK economic growth. Overall, government spending at all three levels of disaggregation is documented to influence the economic growth in the UK. In this aspect, the results move along with the endogenous growth literature. However, in a policy making framework, the disclosed nonlinearity patterns stress the high risk involved whenever economic growth is pursued restrictively via public spending policies overlooking other important elements of the economic life (e.g. market structure, macroeconomic environment, etc.). Additionally, the exhibited nonlinearity in the examined causality could be regarded as a likely cause of the widespread diversification of the findings in the field empirical literature. Disclaimer: "The views and opinions expressed in this paper are those of the authors and do not necessarily reflect the official position of the affiliated institutions"
Keywords: Nonlinear causality, Economic growth, Government expenditures, UK